A novel supramolecular polymer gel based on naphthalimide functionalized-pillar[5]arene for the fluorescence detection of Hg2+ and I− and recyclable removal of Hg2+via cation–π interactions. Issue 39 (29th August 2017) - Lin, Qi; Mao, Peng-Peng; Fan, Yan-Qing; Liu, Lu; Liu, Juan; Zhang, You-Ming; Yao, Hong; Wei, Tai-Bao
Abstract : By rationally applying cation–π interactions, the supramolecular polymer gel could successively detect Hg 2+ and I − and efficiently remove Hg 2+ from water. Abstract : The development of novel materials for the detection and removal of Hg 2+ is a very important issue due to the acute toxicity of Hg 2+ . Herein, a novel supramolecular polymerP5BD–DPHB has been constructed by the collaboration of a naphthalimide functionalized-pillar[5]arene host (P5BD ) and a bis-bromohexane functionalized-pillar[5]arene guest (DPHB ).P5BD–DPHB could form a stable supramolecular gel (P5BD–DPHB–G ). Interestingly, P5BD–DPHB–G shows selective fluorescent "turn-on" detection for Hg 2+ via cation–π interactions with high selectivity and sensitivity. Furthermore, the Hg 2+ coordinated supramolecular gelP5BD–DPHB–HgG can detect I − successively. The detection limits for Hg 2+ and I − are 1.65 × 10 −9 and 1.84 × 10 −8 mol L −1, respectively. Even more significantly, the xerogel ofP5BD–DPHB–G could remove Hg 2+ from aqueous solution with excellent recyclability and ingestion capacity, and with a Hg 2+ removal rate of 98%.